Analisis Manajemen Persiapan Akreditasi Sekolah dalam Menjamin Mutu Pendidikan di SMK Muhammadiyah 1 Malang - Elfira; Sri Yunita Simanjuntak; Moh. Badrut (Suria Academic Press, 2026)
This study aims to analyze the accreditation preparation management process at SMK Muhammadiyah 1 Malang, and to identify the supporting and inhibiting factors in that process. This research employs a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation, and validated using triangulation techniques. The findings reveal that: (1) The accreditation preparation process at SMK Muhammadiyah 1 Malang was not maximally effective due to the absence of a formal decree (SK) establishing an official accreditation committee. Preparation stages included participation in supervisor-led socialization, completion of instruments based on School Self-Evaluation (EDS) data, and collection of physical evidence such as documents and photographs in accordance with accreditation instruments. (2) The primary supporting factors were the high collective enthusiasm of school members and adequate information technology (IT) competency among teachers. (3) The main inhibiting factors included teachers’ heavy workloads limiting preparation time, and insufficient time allocation for completing the Accreditation Data Entry (DIA) in the Sispena system. Based on these findings, it is recommended that schools strengthen organizational structures through the formation of a formal working team to improve the effectiveness of future accreditation preparation.